Green dreams are made of this: Futures consciousness and proenvironmental engagement - Lalo, Fanny; Ahvenharju, Sanna; Uusitalo, Outi (Wiley, 2025)
Futures consciousness (FC) refers to the capacity to understand, anticipate and prepare for the future. As a form of future orientation, it encompasses five interrelated dimensions of time perspective, agency beliefs, openness to alternatives, systems perception and concern for others. We present here cross-sectional evidence that FC is related to greater environmental engagement, above and beyond other future orientation constructs. In two pre-registered studies (one convenience student sample and one representative sample; N = 1041), we found that respondents with higher futures consciousness reported greater proenvironmental behaviour (consumption behaviour, land stewardship, social environmentalism and environmental citizenship). FC proved a better predictor of proenvironmental behaviour than the Zimbardo Inventory's Future Time Perspective and the Consideration for Future Consequences Scale (Study 1). FC was also related to stronger biospheric values (Study 2). However, it was not significantly related to personal environmental footprint (derived from a 16-item calculator). Strikingly, the environmental footprint was also unrelated to the Proenvironmental Behaviour Scale, which could point to a lack of correspondence between measures of proenvironmental propensity and impact. We discuss implications for future-thinking research and interventions aiming to improve futures consciousness.